Sport Policy in Canada - Jean Harvey
Sport Policy in Canada provides the first and most comprehensive analysis of the new Canadian Sport Policy adopted in 2012. In light of this new policy, the authors, top scholars in the field, provide detailed accounts of the most salient sport policies and programs, while also discussing issues and challenges facing policy makers. In Canada and around the world, the last decades have known a sharp increase in state intervention and public funding in pursuit of medals on the international stage and in support of a more active lifestyle. Governments at all levels have made substantial investments in hope of hosting major sporting events to benefit from the economic impact and gain international prestige.The study of sport policies, often neglected in the past, is becoming an increasingly important research topic. Sport Policy in Canada seeks to fill this void by offering the most comprehensive analysis of sport policy since Macintosh, Bedecki, and Franks' Sport Policy in Canada (1987).